2001
DOI: 10.1248/bpb.24.1064
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Interaction of Bisphenol A in Human Hepatic Cytochrome P450 and Steroidogenic CYP17.

Abstract: Bisphenol A (4,4Ј-isopropylidenediphenol, BPA) is widely used in the chemical industry in the manufacturing of epoxy, polycarbonate, and polyester-styrene resins, and trace levels of BPA leach from polycarbonate plasticware and resins used for food packaging materials. This compound is suspected to be an endocrine disrupter. 2) Additionally, it has been reported that exposure of male rats and mice to BPA may be associated with increased incidence of cancers of the hematopoietic system and that high doses of BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…9,10) We have reported that bisphenol A exhibited a noncompetitive-type inhibition of aminopyrine N-demethylation by CYP2C8, a mixed-type inhibition of S-mephenytoin 4Ј-hydroxylation by CYP2C19, and a competitive-type inhibition of progesterone 17a-hydroxylation by CYP17 with K i values of 97, 113, and 71 mM, respectively. 16,17) The K i values of nonylphenol on diclofenac 4Ј-hydroxylaytion by CYP2C9, Smephenytoin 4Ј-hydroxylation by CYP2C19 and progesterone 17a-hydroxylation by CYP17 were 5.3 mM, 37 mM and 62 mM, respectively (Figs. 2-4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,10) We have reported that bisphenol A exhibited a noncompetitive-type inhibition of aminopyrine N-demethylation by CYP2C8, a mixed-type inhibition of S-mephenytoin 4Ј-hydroxylation by CYP2C19, and a competitive-type inhibition of progesterone 17a-hydroxylation by CYP17 with K i values of 97, 113, and 71 mM, respectively. 16,17) The K i values of nonylphenol on diclofenac 4Ј-hydroxylaytion by CYP2C9, Smephenytoin 4Ј-hydroxylation by CYP2C19 and progesterone 17a-hydroxylation by CYP17 were 5.3 mM, 37 mM and 62 mM, respectively (Figs. 2-4).…”
Section: Discussionmentioning
confidence: 99%
“…16,17) In the present study, we investigated the inhibitory effect of nonylphenol on hepatic CYPs and steroidogenic CYP17 using the cDNA-expressed P450s.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…CYP enzymes are also involved with the metabolism of nonylphenols [220]. Similarly, BPA is mainly metabolized by the CYP2C subfamily in the liver [221]. Thus, impaired CYP function due to glyphosate exposure [11,157,158] can be expected to interfere with metabolism of PCBs and therefore increase their oestrogenic potential, leading indirectly to increased risk of breast cancer.…”
Section: Breast Cancermentioning
confidence: 99%